2018
DOI: 10.4236/jct.2018.96041
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Conformal Radiotherapy Concurrently with Paclitaxel/Carboplatin in Gastric Cancer

Abstract: Background and objectives: Surgery is the primary therapy for localized gastric cancer, but even with the best results only 40% 5-year survival can be achieved with the use of postoperative adjuvant chemoradiotherapy. Preoperative therapy might help increase the R0 resection rate, which is an independent predictor of 5-year OS. Our study hypothesized that the concurrent combination of carboplatin-paclitaxel with radiation therapy would result in a pathological CR rate, which will be in turn associated with OAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ahmed et al included 32 patients with GC who received NCRT. The pCR rate was 18.8% and the 2-year OS was 51.3% [ 30 ]. Although, some phase II clinical trial has found the value of NCRT in middle and distal GC, it still needs evidence from larger sample size prospective clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al included 32 patients with GC who received NCRT. The pCR rate was 18.8% and the 2-year OS was 51.3% [ 30 ]. Although, some phase II clinical trial has found the value of NCRT in middle and distal GC, it still needs evidence from larger sample size prospective clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Gradually, as D2 resection has become more widespread, the value of adjuvant chemoradiotherapy has been challenged, especially after the results of the ARTIST 2 trial were published [ 5 ]. Recently, some phase II or III studies have verified the value of neoadjuvant radiotherapy for locally advanced GC and EGJ cancer in terms of local control and the R0 reaction rate [ 6 , 7 ]. With advancements in neoadjuvant therapy, the MAGIC, FFCD and FLOT4 trials have confirmed that perioperative chemotherapy will improve patient prognosis [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%